Cellular and Molecular Life Sciences - Bruzzone, Roberto; Eichmann, Klaus; Thomas, Jean-Leon.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
The multidisciplinary, peer reviewed Open Access journal Cellular and Molecular Life Sciences (CMLS) publishes research articles, reviews, multi-author reviews and visions & reflections articles covering the latest aspects of biological and biomedical research. The journal will consider contributions focusing on biochemistry and molecular biology, cell biology, molecular and cellular aspects of biomedicine, neuroscience, pharmacology and immunology. Manuscripts covering preclinical models in any of these areas will be considered. In addition, CMLS welcomes comments on any article published in CMLS, as well as suggestions for topics to be covered.
Keywords: Cytology; Medicine$1 (BResearch.s; Biology$1 (BResearch.s; Life sciences; Biochemistry; Cell Biology; Biomedical Research; Life Sciences; Chemical Biology